Modelo integrado de custo total de propriedade (TCO) e multicritério para gestão do agronegócio familiar - Lizot, Mauro (2022)
Family agribusiness is a pillar for the basic structure of global food production, which generates the need for cost management to direct decisions in the process of selecting suppliers and inputs. The decision-making process to improve family agribusiness depends exclusively on the planning and understanding of all existing resources in cost management in order to select the most suitable suppliers. As a research problem, there is a lack of specific models for decision making in the acquisition and management of inputs and services in family agribusiness that can be based on Total Cost of Ownership (TCO) combined with Multicriteria Methods. To fill this gap, the objective of this work was to develop an integrated decision-making model for the acquisition of inputs and services, based on the Total Cost of Ownership method and Multicriteria Methods in family agribusiness. The methodology was based on a structured model composed of seven phases, involving multi-criteria methods (AHP and MABAC) and TCO, with monetary and non-monetary criteria, which represent all hidden costs related to rural activity in family agribusiness. The application of the model took place in corn production crop properties, with the chemical fertilizer input, common to all surveyed properties. Data were collected from 11 suppliers in Brazil and five suppliers in Portugal. The main results showed that from the 11 suppliers analyzed for the supply of chemical fertilizer input, in the Southern Region of Brazil and the five suppliers analyzed in the Northern Region of Portugal, it is possible to form a ranking of priorities, with benefits for farmers in decision making in the act of acquisition. The proposed model proved to be relevant in the application to the context in which it was created, but the main advantage is that the model proved to be replicable for other environments and contexts as it recognizes a wide set of criteria and is flexible for inclusion or exclusion of criteria for decision. The social implications highlighted by the study are the improvement of the quality of life of families with productivity and financial gains, in addition to the possibility of investments and development of new rural activities, consequently increasing the quality of the products cultivated by rural owners.